Hormonal status of patients with external genital endometriosis combined with hypothyroidism - B.M. Lysenko; B.V. Khabrat; O.O. Lytvak; O.Ya. Giryavenko; T.A. Struk; А.A. Gordejchuk; A.B. Khabrat (Клінічна та профілактична медицина, 2019)
Objective – to determine the hormonal status of patients with genital endometriosis combined with hypothyroidism.